Transcriptome Analysis of Lungs in a Mouse Model of Severe COVID-19 - Cohen-Gihon, Inbar; Israeli, Ofir; Tidhar, Avital; Sapoznikov, Anita; Evgy, Yentl; Stein, Dana; Aftalion, Moshe; Gur, David; Orr, Irit; Zvi, Anat; Sabo, Tamar; Kronman, Chanoch; et al. (Frontiers in Virology, 2022)
Severe manifestations of coronavirus disease 2019 (COVID-19) are mostly restricted to distinct groups of people who have preexisting morbidities. Most COVID-19 animal models develop a mild pathology that resolves within a relatively short period of time, reflecting the more prevalent asymptomatic-to-mild performance of the disease observed in humans. Mice are normally unaffected by SARS coronavirus-2 infection, because of the inability of the virus to bind effectively to the murine angiotensin-converting enzyme 2 (ACE2) receptor. We have previously demonstrated that induction of mild and transient pulmonary morbidity, by application of low doses of ricin, rendered CD1 mice to be susceptible to this virus, which was displayed by sustained body weight loss and mortality rates >50%. In the present study, we performed transcriptomic analyses charting the major alterations in gene expression of mice that were pre-exposed to low doses of ricin and then subjected to SARS-CoV-2 infection compared to mice that were solely exposed to ricin or infected with SARS-CoV-2. Mice intoxicated and infected with ricin and SARS-CoV-2 demonstrated a marked stimulation of essential immunity genes and biological pathways involved in the activation of natural-killer response, cell death receptors, cytotoxic T-cells, Toll-like receptor signaling and the NLRP3 inflammasome pathway. At the protein level, an induced early and transient interferon response was recorded which was subsequently suppressed. The activation of this array of genes predicts clinical manifestations that are consistent with severe COVID-19 in humans, thereby establishing the suitability of this unique animal model for the study of severe COVID-19 disease.